Different modes of enhancer-specific regulation by Runt and Even-skipped during Drosophila segmentation - Hang, Saiyu (Mol Biol Cell, 2017)
The initial metameric expression of the Drosophila sloppy paired 1 (slp1) gene is controlled by two distinct cis-regulatory DNA elements that interact in a nonadditive manner to integrate inputs from transcription factors encoded by the pair-rule segmentation genes. We performed chromatin immunoprecipitation on reporter genes containing these elements in different embryonic genotypes to investigate the mechanism of their regulation. The distal early stripe element (DESE) mediates both activation and repression by Runt. We find that the differential response of DESE to Runt is due to an inhibitory effect of Fushi tarazu (Ftz) on P-TEFb recruitment and the regulation of RNA polymerase II (Pol II) pausing. The proximal early stripe element (PESE) is also repressed by Runt, but in this case, Runt prevents PESE-dependent Pol II recruitment and preinitiation complex (PIC) assembly. PESE is also repressed by Even-skipped (Eve), but, of interest, this repression involves regulation of P-TEFb recruitment and promoter-proximal Pol II pausing. These results demonstrate that the mode of slp1 repression by Runt is enhancer specific, whereas the mode of repression of the slp1 PESE enhancer is transcription factor specific. We propose a model based on these differential regulatory interactions that accounts for the nonadditive interactions between the PESE and DESE enhancers during Drosophila segmentation.